Excitation spectra of liquid iron up to superhigh temperatures. (31st July 2017) - Fomin, Yu D; Ryzhov, V N; Tsiok, E N; Brazhkin, V V
Abstract: Investigation of excitation spectra of liquids is one of the hot test topics nowadays. In particular, recent experimental works showed that liquid metals can demonstrate transverse excitations and positive sound dispersion. However, the theoretical description of these experimental observations is still missing. Here we report a molecular dynamics study of excitation spectra of liquid iron. We compare the results with available experimental data to justify the method. After that we perform calculations for high temperatures to find the location of the Frenkel line introduced in our previous works.